Filsafat Idealisme Immanuel Kant: Relevansinya dalam Pendidikan Karakter di Sekolah Dasar: Immanuel Kant's Philosophy of Idealism: Its Relevance in Character Education in Elementary Schools - Gumilar, Gumgum; Saifudin, M. Fakhri; Fauziati, Endang; Muhibbin, A. (Undiksha, 2024)
Education is very important to build individuals who are in accordance with the values and culture of their society. The purpose of this study is to describe the relevance of Immanuel Kant's Idealism Philosophy in character education in elementary schools. Kant's view of this philosophy shows how important it is to build the intellect, stick to objective moral principles, and respect human dignity. The purpose of this character education is to produce people who have good character, reason, and act morally in everyday life. This study uses qualitative research with a literature approach through purposive sampling technique. Books, journals, papers, articles, and other scientific works relevant to the research subject are used in this study. The data analysis process uses the content analysis method that focuses on Kant's Idealism theory in teaching character education in elementary schools. The results show that the purpose of character education in elementary schools is to foster students' ethics, morals, values and characters. Some of the main values of character education emphasized by Immanuel Kant's philosophy of idealism are as follows: curiosity, national spirit, and love for the country, religion, honesty, tolerance, discipline, hard work, creativity, independence, environmental care, social care, responsibility, and love to read. Character education is very important to build students' character and make elementary school a good place to learn.